Comprehensive assessment of induced seismicity and its implications for the Atatürk dam: Insights from trenching, seismic investigations, and paleo-stress analysis along the Bozova fault in the East Anatolian tectonic regime, Southeast Türkiye - Kocbulut, Fikret; Softa, Mustafa; Akgun, Elif; Kosaroglu, Sinan; Efe, Ahmet (Science Press, 2025)
Earthquakes are predominantly associated with tectonically active regions, yet the rising frequency of seismic events globally has raised concerns about the role of industrial activities, such as fluid injection, conventional oil-gas, mining, and reservoir impoundment, in triggering significant earthquakes. While natural processes like tectonic stress changes, fluid migration, and surface loading are critical in earthquake nucleation, human-induced seismicity is becoming increasingly recognized. The Atat & uuml;rk Dam, T & uuml;rkiye's largest clay-core rockfill dam, situated near the East Anatolian Fault System, Adiyaman Fault Zone, and Bozova Fault, offers a compelling case to explore the interplay between tectonic and anthropogenic seismicity. This study presents the first trenching studies along the Bozova Fault, revealing evidence of surface ruptures and localized seismicity linked to reservoir impoundment and conventional oil and gas. Temporal and spatial analyses suggest that reservoir-induced mechanisms, including pore pressure diffusion and stress redistribution, significantly influence seismicity, recurrence interval, alongside dominant tectonic forces. By integrating trenching investigations, seismic analyses, and stress inversion techniques, this research highlights the critical role of anthropogenic factors in modulating seismic hazards. The findings emphasize the importance of paleoseismological and geophysical studies for distinguishing induced seismicity from natural tectonic activity, thereby contributing to improved seismic hazard assessment and mitigation strategies in tectonically active, reservoir-influenced regions.
Keywords: Induced seismicity; Bozova fault; Atat & uuml;rk dam; Earthquake mitigation